2012
DOI: 10.1074/jbc.m112.358283
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Cell Wall Polymers of Enterococcus faecalis Are Critical for Resistance to Complement Activation via Mannose-binding Lectin

Abstract: Background:Little is known about the complement evasion strategies of Enterococcus faecalis. Results: Inactivation of tagB in E. faecalis V583 resulted in the loss of two wall teichoic acids (WTAs) associated with a strongly increased complement deposition by the lectin pathway. Conclusion: WTA is critical for complement evasion in E. faecalis. Significance: WTA biosynthesis may be a valuable target for novel antimicrobial agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 51 publications
2
40
0
Order By: Relevance
“…Bacterial surface polysaccharides directly interact with mammalian host surfaces and are key virulence factors (17, 34, 37-41). Previous studies identified glucose, rhamnose, N -acetylglucosamine, N -acetyl galactosamine, and galactose as major components of Epa (17, 34); however, there are gaps in our understanding of the Epa cell surface architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial surface polysaccharides directly interact with mammalian host surfaces and are key virulence factors (17, 34, 37-41). Previous studies identified glucose, rhamnose, N -acetylglucosamine, N -acetyl galactosamine, and galactose as major components of Epa (17, 34); however, there are gaps in our understanding of the Epa cell surface architecture.…”
Section: Discussionmentioning
confidence: 99%
“…WTAs have a very complex structure, which is distinct from that of S. aureus or Listeria. Of note, E. faecalis or E. faecium produce different WTAs with hexose-containing repeating units (GalNAc-RboP glycosylated with ␣-linked rhamnose or Glc-GalNAc-RboP glycosylated with ␣-linked Glc, both WTAs found in E. faecalis V583 whereas non-substituted GalNAc-GroP, type WTA was found in E. faecium U0317) (Bychowska et al, 2011;Geiss-Liebisch et al, 2012) (Table 1). Although some functions of Enterococcus WTAs including evasion from the lectin pathways of the human complement system have recently been described (Geiss-Liebisch et al, 2012) it still has to be elucidated how and why enterococci glycosylate their WTA.…”
Section: Role Of Wta Glycosylation In Other Gram-positive Bacteriamentioning
confidence: 99%
“…Of note, E. faecalis or E. faecium produce different WTAs with hexose-containing repeating units (GalNAc-RboP glycosylated with ␣-linked rhamnose or Glc-GalNAc-RboP glycosylated with ␣-linked Glc, both WTAs found in E. faecalis V583 whereas non-substituted GalNAc-GroP, type WTA was found in E. faecium U0317) (Bychowska et al, 2011;Geiss-Liebisch et al, 2012) (Table 1). Although some functions of Enterococcus WTAs including evasion from the lectin pathways of the human complement system have recently been described (Geiss-Liebisch et al, 2012) it still has to be elucidated how and why enterococci glycosylate their WTA. Similar to enterococci streptococci such as Streptococcus pneumoniae synthesize very complex polymers with identical repeating units in WTA and LTA, which are glycosylated with GalNAc (Denapaite et al, 2012) (Table 1) although recent studies on S. pneumoniae LTA suggest no any glycosylation, possibly its WTA was not glycosylated either (Gisch et al, 2013).…”
Section: Role Of Wta Glycosylation In Other Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly pathways and functions of WTA and LTA of enterococci have not yet been thoroughly studied and elucidated. However, inactivation of the tagB gene in E. faecalis V583 leads to abrogation of the synthesis of two WTAs, which was associated with an increased susceptibility to complement-mediated killing by neutrophils [100]. In other Gram-positive microbes, WTAs entail many different functions including attachment to host tissues, cell division or abscess formation, and may be a target for opsonic antibodies [89].…”
Section: µMmentioning
confidence: 99%